Self-supporting nickel atom modified copper-based composite electrode and preparation method and application thereof
By modifying the copper-based composite electrode by self-supporting nickel atoms, the safety hazards of traditional PZT synthesis methods and the poor conductivity of MOFs electrocatalysts are solved, and the efficient and stable electrocatalytic 5-ATOR process is achieved, and the electrode preparation process is simplified.
Patent Information
- Application Number
- CN202310986097.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional organic synthesis methods used for PZT synthesis have the problem of using strong oxidants and organic reagents, which leads to corrosiveness, toxicity, high cost and difficult to remove by-products. The reaction usually needs to be carried out under heating conditions, which poses safety risks. At the same time, when used as an electrocatalyst, MOFs face problems such as poor conductivity and insufficient structural stability.
The copper-based composite electrode is modified by self-supporting nickel atoms. The electrode material includes a Ni atom-modified CuO nanosheet array and a copper-based metal substrate. It is prepared by electrodeposition, chemical adsorption and in-situ electrochemical conversion methods to form a three-dimensional open porous structure. electrode.
This electrode material significantly reduces over-applied voltage during electrocatalyzing 5-ATOR, improves the conductivity and stability of the electrode, avoids the use of adhesives, simplifies the preparation process, and achieves a larger amount of time during the catalytic process. Current density.
Smart Images

Figure CN119433593A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and relates to a self-supporting nickel atom-modified copper-based composite electrode and a preparation method and application thereof, and specifically relates to an electrode material for organic small molecule conversion and a preparation method thereof and for electrosynthesis of 5,5'-nitrogen tetrazolate. Background Art
[0002] In today's society, the extensive use of traditional fossil energy has led to increasingly serious environmental and energy problems, which has forced people to urgently find and use clean, sustainable and environmentally friendly energy. Hydrogen energy is considered to be an ideal substitute for traditional fossil fuels due to its advantages such as high energy density and zero carbon emissions. Among various hydrogen production strategies, water electrolysis hydrogen production technology has attracted great attention due to its high product (hydrogen) purity and sustainable development. The water electrolysis process usually contains two half reactions, namely the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. However, the OER process faces problems such as slow reaction kinetics, high thermodynamic potential, and low product (oxygen) added value, which will seriously limit the overall efficiency and economic benefits of water electrolysis hydrogen production. In the process of water electrolysis, replacing OER with thermodynamically more favorable organic small molecules (such as methanol, ethanol, benzyl alcohol, 5-hydroxymethylfurfural, ethylene glycol, glycerol, isopropanol, glucose and 5-amino-1H-tetrazole (5-AT), etc.) oxidation reactions can not only significantly reduce energy consumption, but also be expected to obtain higher value-added oxidation products at the anode. Among them, it is an ideal solution to replace OER with 5-AT oxidation reaction (5-ATOR) to construct an electrolytic water system. It can not only reduce the energy consumption of hydrogen evolution, but more importantly, the 5,5'-azoazole (ZT) potassium salt (PZT) product can be obtained through the 5-ATOR process. PZT is often used as a material for military and industrial applications due to its high energy density, high propulsion, low flame and high formation heat enthalpy. However, traditional organic synthesis methods for PZT synthesis usually require a series of strong oxidants and organic reagents, most of which have the disadvantages of corrosiveness, toxicity, high cost and difficult removal of by-products. In addition, these reactions usually need to be carried out under heating conditions, which poses a great safety hazard.
[0003] Metal-organic frameworks (MOFs) are a new type of porous crystalline materials, which are formed by the connection of metal centers and organic ligands. They have the advantages of large specific surface area, clear structure and flexible adjustability, and are widely used in catalysis, adsorption and energy storage. However, when MOFs are used as electrocatalysts in the field of electrocatalysis, most of them face problems such as poor conductivity and insufficient structural stability. Using MOFs as precursors, MOFs-derived electrocatalysts prepared by a series of strategies (such as high-temperature calcination, (electro)chemical conversion, etc.) can significantly improve the corresponding catalytic performance, but these processes are usually complicated, time-consuming, and have low reproducibility. At the same time, MOFs and their derivatives prepared by conventional routes are usually in powder form, which requires the addition of binders when they are made into electrodes for electrocatalytic reactions, making it difficult to obtain ideal electrocatalytic performance. Therefore, developing an efficient and economical method to prepare integrated MOFs-derived electrode materials with excellent electrocatalytic performance is of great significance to realize the large-scale industrial application of electrosynthesized PZT. Summary of the invention
[0004] In order to improve the above technical problems, the present invention provides a self-supporting nickel atom modified copper-based composite electrode and its preparation method and application. The electrode material of the present invention can be used for the electrosynthesis of PZT, and can ensure the stability of the electrode material while achieving efficient electrocatalysis of 5-ATOR.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] The present invention provides an electrode material, which contains copper, nickel and oxygen. Preferably, the electrode material comprises a CuO nanosheet array modified by Ni atoms and a substrate, and the CuO nanosheets modified by Ni atoms are in-situ grown on the surface of the substrate.
[0007] According to an embodiment of the present invention, the loading amount of Ni atoms is 0.01-5wt%, exemplified by 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, and 5wt%.
[0008] According to an embodiment of the present invention, the loading amount of the CuO nanosheet array on the substrate is 0.01-5 mg / cm 2 , exemplified by 0.01 mg / cm 2 , 0.05mg / cm 2 , 0.1mg / cm 2 , 0.5mg / cm 2 , 1mg / cm 2 , 2mg / cm 2 、3mg / cm2 , 4mg / cm 2 , 5mg / cm 2 .
[0009] According to an embodiment of the present invention, the substrate is a copper-based metal substrate, such as at least one of foamed copper, copper mesh, copper foil, copper sheet, copper rod and copper wire.
[0010] Exemplarily, the electrode material contains CuO nanosheet arrays modified with Ni atoms (Ni-CuO) and copper foam (CF), represented by Ni-CuO-CF, and the Ni-CuO is in-situ grown on the surface of the copper foam (CF) substrate.
[0011] According to an embodiment of the present invention, the electrode material has a three-dimensional open porous structure consisting of CuO two-dimensional nanosheet arrays modified by Ni atoms.
[0012] The present invention also provides a method for preparing the above electrode material, comprising the following steps:
[0013] An electrolyte, an organic solution and an organic ligand are mixed to obtain a mixed solution, a substrate is placed in the mixed solution, a precursor Cu-MOF is modified on the surface of the substrate through an electrodeposition reaction, and then the substrate is placed in a nickel salt solution for chemical adsorption. Finally, an electrode material having a CuO nanosheet array modified with Ni atoms grown on the surface of the substrate is obtained through an in-situ electrochemical conversion method.
[0014] According to an embodiment of the present invention, in the mixed solution, the concentration of the electrolyte is 0.1-0.5 g / L, exemplarily 0.3 g / L.
[0015] According to an embodiment of the present invention, the electrolyte is selected from one or more of tetrabutylammonium perchlorate, tetrabutylammonium fluoroborate, tetraethylammonium perchlorate and lithium perchlorate.
[0016] According to an embodiment of the present invention, the organic solution is a mixed solution of an organic solvent and deionized water. For example, the organic solvent is selected from one or more of methanol, ethanol, acetonitrile, ethylene glycol, dimethyl sulfoxide, N,N-dimethylformamide and N,N-dimethylacetamide. Preferably, the volume ratio of the organic solvent to water is 1:9 to 9:1.
[0017] According to an embodiment of the present invention, in the mixed solution, the concentration of the organic ligand is 0.01 to 1 mol / L, exemplarily 0.05 mol / L.
[0018] According to an embodiment of the present invention, the organic ligand is selected from one or more of 1,3,5-benzenetricarboxylic acid, 1,4-terephthalic acid, 2-aminoterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,6-pyridinedicarboxylic acid, imidazole-4,5-dicarboxylic acid and 3,4-pyridinedicarboxylic acid.
[0019] According to an embodiment of the present invention, the substrate is a copper-based metal substrate, such as at least one of copper foam (CF), copper mesh, copper foil, copper sheet, copper rod and copper wire.
[0020] According to an embodiment of the present invention, the substrate may be pretreated before electrodeposition to remove the oxide layer and organic residues on the metal surface. The pretreatment method may be: immersing the substrate in an acid (e.g., dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid), an organic solvent (e.g., methanol, ethanol, acetone, etc.) and water (e.g., deionized water) in sequence for ultrasonic washing, and then drying.
[0021] According to an embodiment of the present invention, during the electrodeposition process, the electrolytic current is 0.1 to 100 mA, exemplarily 5 mA; the electrodeposition time is 1 to 1*10 6 s, exemplarily 5000s.
[0022] According to an embodiment of the present invention, the concentration of the nickel salt (e.g., Ni(NO3)2·6H2O) solution is 0.01 to 2.0 mol / L, exemplified by 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1.0 mol / L, and 2.0 mol / L; the adsorption time is 0.01 to 24 h, exemplified by 0.01 h, 0.1 h, 1 h, 2 h, 6 h, 12 h, and 24 h.
[0023] According to an embodiment of the present invention, during the in-situ electrochemical conversion process, the potential scanning window of the cyclic voltammetry is between -2.0 and 2.0 V vs. Ag / AgCl; the scanning rate is 1 to 100 mV / s; and the number of scanning cycles is 1 to 200 cycles.
[0024] According to an embodiment of the present invention, after the in-situ electrochemical conversion is completed, the product is further washed. For example, the product is washed multiple times using water (such as deionized water) and ethanol in sequence.
[0025] According to an embodiment of the present invention, the preparation method further comprises drying at 50-70° C. after washing.
[0026] According to an exemplary embodiment of the present invention, the method for preparing the electrode material comprises the following steps:
[0027] a) mixing the electrolyte, the organic ligand and the organic solution, adding the pretreated substrate, and performing constant current electrodeposition using a three-electrode system to obtain a Cu-MOF precursor;
[0028] b) immersing the obtained Cu-MOF precursor in an ethanol solution of Ni(NO3)2 to obtain Ni-modified Cu-MOF, and then performing in-situ electrochemical conversion by cyclic voltammetry to obtain the electrode material.
[0029] The present invention also provides an electrode, the electrode containing copper, nickel and oxygen. Preferably, the electrode comprises a CuO nanosheet array modified by Ni atoms and a substrate, and the CuO nanosheet modified by Ni atoms is in-situ grown on the surface of the substrate.
[0030] According to an embodiment of the present invention, the loading amount of Ni atoms is 0.01-5wt%, exemplified by 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, and 5wt%.
[0031] According to an embodiment of the present invention, the loading amount of the CuO nanosheet array on the substrate is 0.01-5 mg / cm 2 , exemplified by 0.01 mg / cm 2 , 0.05mg / cm 2 , 0.1mg / cm 2 , 0.5mg / cm 2 , 1mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 .
[0032] According to an embodiment of the present invention, the substrate is a copper-based metal substrate, such as at least one of foamed copper, copper mesh, copper foil, copper sheet, copper rod and copper wire.
[0033] Exemplarily, the electrode includes a CuO nanosheet array modified with Ni atoms (Ni-CuO) and copper foam (CF), represented by Ni-CuO-CF, and the Ni-CuO is in-situ grown on the surface of the copper foam (CF) substrate.
[0034] According to an embodiment of the present invention, the electrode has a three-dimensional open porous structure consisting of a CuO two-dimensional nanosheet array modified with Ni atoms.
[0035] According to an embodiment of the present invention, the electrode is a self-supporting electrode.
[0036] The present invention also provides the use of the above-mentioned electrode material and / or electrode in a water electrolysis hydrogen production system, an oxidation reaction of environmental sewage treatment, an organic small molecule upgrading reaction, etc. Preferably, the electrode material and / or electrode is applied to a water electrolysis hydrogen production system coupled with an organic small molecule oxidation reaction. Exemplarily, it is applied as a self-supporting electrode to the electrosynthesis of 5,5'-azoazole (ZT) potassium salt (PZT) in the 5-amino-1H-tetrazole (5-AT) oxidation reaction (5-ATOR).
[0037] According to an embodiment of the present invention, the size of the electrode is (0.5 x 0.5) to (10 x 10) cm 2 .
[0038] According to an embodiment of the present invention, the concentration of 5-AT is 0.01 to 3.0 mol / L, exemplarily 0.2 mol / L.
[0039] In the present invention, the 5-ATOR product can be characterized by UV-visible absorption spectroscopy. Furthermore, the electrolyzed solution has the same absorption peak as standard PZT at 420 nm, corresponding to the n-π* band of the azo group in the target product PZT.
[0040] In the present invention, the 5-ATOR product can be further characterized by nuclear magnetic resonance (NMR) spectroscopy to determine whether it is a pure phase. Furthermore, the electrolyzed solution is 13 The chemical shift of δ = 171.78 ppm in the C NMR spectrum corresponds to the tetrazolyl carbon in the target product PZT. 1 The H NMR chemical shift at δ = 4.70 ppm corresponds to adsorbed water in the target product PZT.
[0041] Beneficial effects of the present invention:
[0042] (1) In the electrode material provided by the present invention, the Ni-CuO nanosheet array is in-situ grown on the surface of the metal substrate, and the two are in close and firm contact. Using it as an electrode material for electrocatalysis of 5-ATOR can enhance the overall conductivity and stability of the electrode.
[0043] (2) The electrode material provided by the present invention has a three-dimensional open porous structure composed of a two-dimensional nanosheet array, which can not only expose more catalytic active sites, but also facilitate the penetration of electrolytes to promote electron and proton transfer, thereby accelerating the catalytic reaction kinetics.
[0044] (3) The electrode material provided by the present invention can be directly used as a self-supporting electrode for electrocatalysis of 5-ATOR, avoiding the use of adhesives, reducing the electrode preparation steps, and being simple and quick.
[0045] (4) The electrode material provided by the present invention can significantly reduce the over-applied voltage when applied to the electrocatalytic 5-ATOR. When the output current density is 100 mA cm –2 The required applied voltage is 367 mV lower than that of OER, and it has a smaller Tafel slope and electrochemical impedance.
[0046] (5) The electrode material provided by the present invention uses a copper-based metal substrate as a raw material and combines electrodeposition, chemical adsorption and in-situ electrochemical conversion. It has low cost, simple operation, excellent performance, and can achieve a large current density during the catalytic process. This makes the electrode material have broad application prospects in the fields of organic small molecule conversion and energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the X-ray diffraction pattern of the Ni-CuO-CF self-supporting electrode prepared in Example 1.
[0048] Figure 2 These are scanning and transmission electron microscope images of the Ni-CuO-CF self-supporting electrode prepared in Example 1 and the CuO-CF self-supporting electrode prepared in Example 2.
[0049] Figure 3 It is a high-magnification transmission electron microscope image of the Ni-CuO-CF self-supporting electrode prepared in Example 1 and the CuO-CF self-supporting electrode prepared in Example 2.
[0050] Figure 4 It is the X-ray photoelectron spectrum of the Ni-CuO-CF self-supporting electrode prepared in Example 1 and the CuO-CF self-supporting electrode prepared in Example 2.
[0051] Figure 5 This is a polarization curve diagram of the product in Example 1 obtained using linear sweep voltammetry (LSV).
[0052] Figure 6 This is a constant current stability test chart of the product of Example 1. DETAILED DESCRIPTION
[0053] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0054] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0055] The instrument information used in the following examples is shown in Table 1, and the reagent information used in the examples is shown in Table 2.
[0056] Table 1. Instrument information table used in the examples
[0057]
[0058] Table 2. Information of reagents used in the examples
[0059]
[0060] Example 1
[0061] (1) Pretreatment of the substrate: 2 x 2 cm 2 The foamed copper (CF) was immersed in dilute hydrochloric acid (1.0 mol / L), ethanol and deionized water for ultrasonic washing to remove the surface oxide layer and organic residues, and then placed in an oven at 60°C for drying.
[0062] (2) 20 mL of a water / ethanol mixed solution containing 0.05 mol / L 1,3,5-benzenetricarboxylic acid and 0.3 g / L tetrabutylammonium perchlorate (the volume ratio of water to ethanol was 1:1) was added to a beaker (30 mL). Then, the CF pretreated in step (1) was used as the working electrode, and a Pt mesh (1.0 x 1.0 cm 2 ) was used as the counter electrode, and the saturated Ag / AgCl electrode was used as the reference electrode. The Cu-MOF self-supporting electrode (Cu-MOF-CF) was obtained by constant current electrodeposition at 5 mA for 5000 s, and then vacuum dried for 12 h.
[0063] (3) The Cu-MOF-CF prepared in step (2) was used as a precursor and immersed in a 0.1 mol / L Ni(NO3)2 ethanol solution for 12 h to obtain a Ni-modified Cu-MOF-CF electrode. Then, the electrode was subjected to cyclic voltammetry (scan rate: 30 mV / s) in 1.0 mol / L KOH in the range of -1 to 0.8 V vs. Ag / AgCl for 15 cycles until the curves overlapped, thereby obtaining a Ni-CuO-CF self-supporting electrode.
[0064] Example 2
[0065] (1) Pretreatment of the substrate is the same as step (1) of Example 1.
[0066] (2) The Cu-MOF-CF sample was prepared by electrodeposition, which was the same as step (2) of Example 1.
[0067] (3) The Cu-MOF-CF prepared in (2) was used as a precursor, and then cyclic voltammetry (scan rate: 30 mV / s) was performed in 1.0 mol / L KOH in the range of -1 to 0.8 V vs. Ag / AgCl for 15 cycles until the curves overlapped, thereby obtaining a CuO-CF self-supporting electrode.
[0068] (I) Structural characterization of the products of Example 1-2
[0069] The product obtained in Example 1 was analyzed by X-ray powder diffraction. Figure 1 (a) is the theoretical powder X-ray diffraction pattern of CuO. Figure 1 (b) is the powder X-ray diffraction pattern of the Ni-CuO-CF electrode obtained in Example 1. As can be seen from the figure, the XRD spectrum of the Ni-CuO-CF electrode obtained in Example 1 is basically consistent with the theoretical spectrum. This shows that the CuO nanosheet array modified with Ni atoms grows on the surface of the CF substrate in Example 1.
[0070] Figure 2 The following are scanning and transmission electron microscope images of the products of Example 1 and Example 2. Figure 2 (a) is a scanning electron microscope image of the product of Example 1, Figure 2 (b) is a scanning electron microscope image of the product of Example 2, Figure 2 (c) is a transmission electron microscope image of the product of Example 1. Figure 2 (d) is a transmission electron microscope image of the product of Example 2. It can be clearly seen from the figure that the CuO nanosheets in the CuO-CF electrode prepared in Example 2 grow closely and evenly on the surface of the CF substrate, while after Ni doping modification in Example 1, the morphology of the CuO nanosheets in the Ni-CuO-CF electrode does not change significantly.
[0071] Figure 3 (a) and Figure 3 (b) are high-resolution transmission electron microscopy images of the products of Example 1 and Example 2. Figure 3 In (b), lattice fringes with a lattice spacing of 0.232 nm are observed, which are the (111) crystal planes of the CuO nanosheets, further confirming that the CuO nanosheet arrays in the CuO-CF electrode grow on the CF substrate. However, it can be observed from Figure 3 (a) that the lattice spacing of CuO in the Ni-CuO-CF electrode becomes 0.248 nm, indicating that the doping modification of Ni regulates the microstructure of the CuO nanosheet arrays.
[0072] Figure 4It is an X-ray photoelectron spectrum of the products of Example 1 and Example 2. The results in the figure confirm the presence of Ni element in the self-supporting electrode of Example 1. Analysis shows that the Ni element is modified on the CuO nanosheets in Ni-CuO-CF at the atomic level. The Ni atom-modified CuO nanosheet array formed by the product of Example 1 can avoid serious aggregation of the catalyst, not only exposing more catalytic active sites, but also facilitating the penetration of electrolytes to promote electron and proton transfer, thereby accelerating the reaction kinetics of the catalysis.
[0073] (II) Electrocatalytic 5-ATOR Performance Test of the Products of Example 1 and Example 2
[0074] The electrocatalytic 5-ATOR performance test of the products of Example 1 and Example 2 was conducted using a three-electrode test system, with the Ni-CuO-CF prepared in Example 1 and the CuO-CF prepared in Example 2 as working electrodes, respectively, with an electrode area of 1.0 x 1.0 cm 2 , Pt mesh (1.0x 1.0cm 2 ) was used as the counter electrode and a saturated Ag / AgCl electrode was used as the reference electrode. The electrolyte was a 1 mol / L KOH solution with 0.2 mol / L 5-AT added. The linear voltammetry (LSV) curve of the sample was obtained at a scan rate of 5 mV / s. The results are shown in Figure 5 As shown in the figure, the Ni-CuO-CF prepared in Example 1 shows better electrocatalytic performance. The starting potential of 5-ATOR is much lower than that of OER, and when the output current density is 100 mA cm -2 Only 1.29 V is required to be applied, which is 367 mV lower than the potential required for OER to output the same current density.
[0075] The Ni-CuO-CF prepared in Example 1 was tested for stability at 10 mA cm -2 The constant current density was maintained for 28 h. The results are as follows Figure 6 As shown. As can be seen from the figure, the test applied potential did not change significantly during the test. It can be seen that the Ni-CuO-CF prepared in Example 1 has high stability as a self-supporting electrode. The above results show that the Ni-CuO-CF prepared in Example 1 has excellent catalytic performance and high stability as a self-supporting electrode, and is one of the best performing 5-ATOR electrocatalysts to date.
[0076] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An electrode material, characterized in that: The electrode material contains copper, nickel and oxygen. Preferably, the electrode material comprises a CuO nanosheet array modified with Ni atoms and a substrate, and the CuO nanosheets modified with Ni atoms are in-situ grown on the surface of the substrate.
2. The electrode material according to claim 1, characterized in that The loading amount of the Ni atoms is 0.01-5 wt %. Preferably, the loading amount of the CuO nanosheet array on the substrate is 0.01-5 mg / cm 2 . Preferably, the substrate is a copper-based metal substrate, such as at least one of foamed copper, copper mesh, copper foil, copper sheet, copper rod and copper wire. Preferably, the electrode material contains CuO nanosheet arrays modified with Ni atoms (Ni-CuO) and copper foam (CF), represented by Ni-CuO-CF, and the Ni-CuO is in-situ grown on the surface of the copper foam (CF) substrate. Preferably, the electrode material has a three-dimensional open porous structure consisting of a CuO two-dimensional nanosheet array modified by Ni atoms.
3. The method for preparing the electrode material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: An electrolyte, an organic solution and an organic ligand are mixed to obtain a mixed solution, a substrate is placed in the mixed solution, a precursor Cu-MOF is modified on the surface of the substrate through an electrodeposition reaction, and then the substrate is placed in a nickel salt solution for chemical adsorption. Finally, an electrode material having a CuO nanosheet array modified with Ni atoms grown on the surface of the substrate is obtained through an in-situ electrochemical conversion method.
4. The preparation method according to claim 3, characterized in that: In the mixed solution, the concentration of the electrolyte is 0.1-0.5 g / L. Preferably, the electrolyte is selected from one or more of tetrabutylammonium perchlorate, tetrabutylammonium fluoroborate, tetraethylammonium perchlorate and lithium perchlorate. Preferably, the organic solution is a mixed solution of an organic solvent and deionized water. For example, the organic solvent is selected from one or more of methanol, ethanol, acetonitrile, ethylene glycol, dimethyl sulfoxide, N,N-dimethylformamide and N,N-dimethylacetamide. Preferably, the volume ratio of the organic solvent to water is 1:9 to 9:
1. Preferably, in the mixed solution, the concentration of the organic ligand is 0.01-1 mol / L. Preferably, the organic ligand is selected from one or more of 1,3,5-benzenetricarboxylic acid, 1,4-terephthalic acid, 2-aminoterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,6-pyridinedicarboxylic acid, imidazole-4,5-dicarboxylic acid and 3,4-pyridinedicarboxylic acid. Preferably, the substrate is a copper-based metal substrate, such as at least one of copper foam (CF), copper mesh, copper foil, copper sheet, copper rod and copper wire.
5. The preparation method according to claim 3 or 4, characterized in that: Before the electrodeposition, the substrate may be pretreated to remove the oxide layer and organic residues on the metal surface. The pretreatment method may be: immersing the substrate in an acid (e.g., dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid), an organic solvent (e.g., methanol, ethanol, acetone, etc.) and water (e.g., deionized water) in sequence for ultrasonic washing, and then drying. Preferably, during the electroplating process, the electrolytic current is 0.1 to 100 mA; the electroplating time is 1 to 10 6 s. Preferably, the concentration of the nickel salt solution is 0.01 to 2.0 mol / L; and the adsorption time is 0.01 to 24 h. Preferably, during the in-situ electrochemical conversion process, the potential scanning window of the cyclic voltammetry is between -2.0 and 2.0 V vs. Ag / AgCl; the scanning rate is 1 to 100 mV / s; and the number of scanning cycles is 1 to 200 cycles.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The method for preparing the electrode material comprises the following steps: a) mixing the electrolyte, the organic ligand and the organic solution, adding the pretreated substrate, and performing constant current electrodeposition using a three-electrode system to obtain a Cu-MOF precursor; b) immersing the obtained Cu-MOF precursor in an ethanol solution of Ni(NO3)2 to obtain Ni-modified Cu-MOF, and then performing in-situ electrochemical conversion by cyclic voltammetry to obtain the electrode material.
7. An electrode, characterized in that: The electrode contains copper, nickel and oxygen. Preferably, the electrode comprises a CuO nanosheet array modified with Ni atoms and a substrate, and the CuO nanosheets modified with Ni atoms are in-situ grown on the surface of the substrate.
8. The electrode according to claim 7, characterized in that The loading amount of the Ni atoms is 0.01-5 wt %. Preferably, the loading amount of the CuO nanosheet array on the substrate is 0.01-5 mg / cm 2 . Preferably, the substrate is a copper-based metal substrate, such as at least one of foamed copper, copper mesh, copper foil, copper sheet, copper rod and copper wire. Preferably, the electrode comprises a CuO nanosheet array modified with Ni atoms (Ni-CuO) and copper foam (CF), represented by Ni-CuO-CF, and the Ni-CuO is in-situ grown on the surface of the copper foam (CF) substrate. Preferably, the electrode has a three-dimensional open porous structure consisting of a CuO two-dimensional nanosheet array modified with Ni atoms. Preferably, the electrode is a self-supporting electrode.
9. Application of the electrode material according to claim 1 or 2 and / or the electrode according to claim 7 in a water electrolysis hydrogen production system, oxidation reaction for environmental wastewater treatment, organic small molecule upgrading reaction, etc.
10. The use according to claim 9, characterized in that The electrode material and / or electrode is applied to a water electrolysis hydrogen production system coupled with an organic small molecule oxidation reaction. Preferably, the present invention is used as a self-supporting electrode for electrosynthesis of 5,5'-azobenzene (ZT) potassium salt (PZT) by 5-amino-1H-tetrazole (5-AT) oxidation reaction (5-ATOR). Preferably, the size of the electrode is (0.5 x 0.5) to (10 x 10) cm 2 . Preferably, the concentration of 5-AT is 0.01 to 3.0 mol / L.